Appreciative Inquiry Principles - Leaders, Coaching (2015)
This article, written by Emotional Intelligence Coach Andy Smith, desc ribes the anticipatory principle which is one of the underpinnings of Appreciative Inquiry (AI). It argues that it is easier and more effect ive to move towards a positive imagined future than away from a negati ve one. It is principle number 4 in a series of principles outlined. M ore principle are listed below.